Layered Intrusions - Charlier, Bernard; Namur, Olivier; Latypov, Rais; Tegner, Christian (Springer Geology, 2015)
This edited work contains the most recent advances related to the study of layered intrusions and cumulate rocks formation. The first part of this book presents reviews and new views of processes producing the textural, mineralogical and geochemical characteristics of layered igneous rocks. The second part summarizes progress in the study of selected layered intrusions and their ore deposits from different parts of the world including Canada, Southwest China, Greenland and South Africa. Thirty experts have contributed to this update on recent research on Layered Intrusions. This highly informative book will provide insight for researchers with an interest in geology, igneous petrology, geochemistry and mineral resources.